Surface morphology, magnetic resonance and antistatic properties of fabric with carbon coating, modified by metal clusters - A. G. Anisovich; I. P. Akula; A. P. Laskovnev; M. I. Markevich; N. M. Chekan (Литьë и металлургия)
The morphology of the surface, the magnetic resonance and antistatic properties of the 07C11-KV blended fabric manufactured by Mogotex LLC with a carbon coating doped with metal clusters are studied.The coating was applied by pulsed cathodic-arc deposition in vacuum of 3.5 · 10–3 Pa. It is established that during the coatinga droplet phase is formed. The size of the drops reaches 20 – 25 microns. The result of measuring the surface resistivity on fabric 1 side / 2 side is 3.2 · 107 and 1.9 · 107 Om, respectively. On the EPR spectrum are recorded two lines. The first line is a broad spectral line with an effective g-factor of 2.27 ± 0.01 and a width of 94.4 mT. The second line is narrow spectral line with an effective g-factor of 2.04 ± 0.01 and a width of 4.3 mT. This is corresponds to carbon coating clusters.From the ratio of the signal intensities of the filled resonator and the calibration sample, it follows that the non-resonant absorption of the microwave electromagnetic field in the system is slightly attenuated.